Tatar Central Asian Narrative of 1905: Petitions Addressed to Central Imperial Structures - Zagidullin, Il’dus K. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
Based on the normative acts of the last third of the 19th century, the author examines the internal policy of the authorities of the steppe regions and Turkestan towards the Tatar population and the reaction of the Tatars to their actions in the initial period of the First Russian Revolution of 1905-1907. They also provide a brief description of the demographic image of Tatar societies in Central Asia. The purpose of the study is to reconstruct the practices of the Tatars of the region in filing petitions and to analyze the texts of petitions in order to identify their needs and aspirations. The participation of a number of Tatar societies of the region in the petition campaign is assessed as a manifestation of their social activity in defending their rights before Imperial structures. In the context of the analysis of the organization of filing petitions by regions, the author reveals: their number (14) and chronological framework, a list of societies/settlements and activistorganizers, dates of petitions and their addressees, and legislative innovations of the autocracy which became the motivation for filing petitions. In addition, the author illustrates the degree of use of model texts from outside and neighboring societies and highlights the forms of filing petitions (by groups or proxies elected at meetings of parish or class societies). They also analyze available sources on such issues as the strengthening and expanding of religion, cultural autonomy, and the establishing additional protection of ethnic confessional and civil rights.